EFFECTS OF DIFFERENT MONTANIDE ADJUVANTS ON TOTAL ERYTHROCYTE COUNTS IN PIGLETS VACCINATED WITH A LOCAL STREPTOCOCCUS SUIS STRAIN - Ni Ketut Suwiti; I Nengah Kerta Besung; Yeocelin Meida Utami (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Streptococcus suis is an important zoonotic pathogen in pigs that causes substantial economic losses and public health concerns. Vaccination using local bacterial strains is considered a promising approach to improve antigenic compatibility and protective immune responses. However, information regarding the effects of different vaccine adjuvants on total erythrocyte counts remains limited. This study aimed to evaluate total erythrocyte counts in piglets vaccinated with an inactivated local S. suis strain formulated with different Montanide™ adjuvants. A total of 12 eight-week-old male Landrace piglets were randomly divided into three groups: control (sterile 0.9% physiological saline), vaccine with Montanide™ ISA 201 VG, and vaccine with Montanide™ Gel 01. Vaccination was administered intramuscularly twice at a 28-day interval. Clinical observations, body weight measurements, and blood sampling were performed weekly for nine weeks. Total erythrocyte counts were analyzed using a VetScan HM5 hematology analyzer, and data were evaluated using repeated measures ANOVA. No significant differences in total erythrocyte counts were observed among treatment groups (p > 0.05). However, observation time significantly affected erythrocyte counts (p < 0.05), with temporary increases occurring during weeks 3 to 5. Overall erythrocyte values remained within normal physiological ranges. In conclusion, inactivated S. suis vaccines formulated with Montanide™ ISA 201 VG and Montanide™ Gel 01 did not significantly affect total erythrocyte counts in Landrace piglets and were well tolerated under the conditions of this study.